Government House, Trinidad - (:unkn) unknown (Stephens Ltd. Trinidad, 2009)
A front view of the Governor's Residence from across the garden where a variety of tropical flora grow and in the back of the main building is the St. Ann's hills.
Colour: Black and White; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Public buildings--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Gardens--Trinidad and Tobago; President's House, The